Avifauna of the Piracicaba Botanical Garden (Santa Rita, Area I), São Paulo and its importance in the restoration and conservation of the Semideciduous Seasonal Forest - Navega-Gonçalves, Maria Eliana Carvalho; Lima, Vosmarline Graziela Rocha; Paulete, Valdir Felipe (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
This study aimed to survey the avifauna of the Piracicaba Botanical Garden (Santa Rita - Area I), São Paulo and to collect data that demonstrates the use of site resources by birds. The survey was conducted between 2020 to 2023 and 131 species were identified, distributed in 18 orders and 41 families, 2 of which are endemic species of the Atlantic Forest. At least 39 bird of the recorded bird species can contribute to the restoration and conservation of the Semideciduous Seasonal Forest, due to their potential for seed dispersal, pollination or both, according to bibliographic references. The area, which is subject to significant anthropic pressures, requires protection and management measures of its spaces and continuous monitoring of avifauna can be an important tool in this process.